An Induced Successful Performance Enhances Student Self-Efficacy and Boosts Academic Achievement - Akitoshi Uchida; Robert B. Michael; Kazuo Mori (SAGE Publishing, 2018)
A growing body of correlational research finds a relationship between self-efficacy-beliefs in one's capabilities-and academic success. But few studies have investigated whether self-efficacy is causally related to academic success. We hypothesized that an experience of success would promote self-efficacy in junior high school students and would lead to academic improvements. To induce an experience of success, we secretly presented easy anagrams to target students (41 males and 43 females; 12-13 years old) who then outperformed their classmates (116 males and 115 females). We assessed students' self-efficacy and academic achievement scores before and after the anagram tasks. We found that the success-induced students raised their self-efficacy, and this elevated self-efficacy persisted for as long as one year. Moreover, success-induced males eventually showed significant improvement in their academic achievement. These results provide a real-world experimental enactment of Bandura's self-efficacy theory and have implications for the practices of educational practitioners.